The dogs of Detroit : stories - Felver, Brad, 1982- (University of Pittsburgh Press, 2018)
"The 14 stories of The Dogs of Detroit each focus on grief and its many strange permutations. This grief alternately devolves into violence, silence, solitude, and utter isolation. In some cases, grief drives the stories as a strong, reactionary force, and yet in other stories, that grief evolves quietly over long stretches of time. Many of the stories also use grief as a prism to explore the beguiling bonds within families. The stories span a variety of geographies, both urban and rural, often considering collisions between the two."--Back cover